Medication eluting devices for the field of OBGYN (MEDOBGYN): 3D printed biodegradable hormone eluting constructs, a proof of concept study - Tappa, Karthik (PLoS One, 2017)
3D printing has the potential to deliver personalized implants and devices for obstetric and gynecologic applications. The aim of this study is to engineer customizable and biodegradable 3D printed implant materials that can elute estrogen and/or progesterone. All 3D constructs were printed using polycaprolactone (PCL) biodegradable polymer laden with estrogen or progesterone and were subjected to hormone-release profile studies using ELISA kits. Material thermal properties were tested using thermogravimetric analysis and differential scanning calorimetry. The 3D printed constructs showed extended hormonal release over a one week period. Cytocompatibility and bioactivity were assessed using a luciferase assay. The hormone-laden 3D printed constructs demonstrated an increase in luciferase activity and without any deleterious effects. Thermal properties of the PCL and hormones showed degradation temperatures above that of the temperature used in the additive manufacturing process–suggesting that 3D printing can be achieved below the degradation temperatures of the hormones. Sample constructs in the shape of surgical meshes, subdermal rods, intrauterine devices and pessaries were designed and printed. 3D printing of estrogen and progesterone-eluting constructs was feasible in this proof of concept study. These custom designs have the potential to act as a form of personalized medicine for drug delivery and optimized fit based on patient-specific anatomy.